A novel estrus-synchronization program for anestrous and cycling, suckled, beef cows - Forbes, W.L.; Corah, L.R.; Thompson, K. E.; Lamb, G.C.; Grieger, David M.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used four herds at three Kansas ranches to evaluate the potential of two new estrus synchronization strategies to increase estrus expression and fertility of 911 crossbred suckled beef cows. The treatments included: 1) 100 μg of GnRH and a 6-mg norgestomet ear implant on day -7 and 25 mg of PG F2" and implant removal on day 0 (GnRH+NORG+PG F2"); 2) 100 μg of GnRH on day - 7 and 25 mg of PGF 2" on day 0 (GnRH+PG F2"); and 3 ) (control) 25- mg injections of PG F2" on days -14 and 0; (2×PGF2" control) . The GnRH+NORG+ PGF 2" and GnRH+PGF treatments increased (P<.01) 2" the overall percentages of cows detected in estrus by 49% and 27% and pregnancy rates by 46% and 37%, respectively, over the control group, without altering conception rate. Both treatments increase d the estrus, conception, and pregnancy rates of noncycling cows, compared to controls.
Keywords: Beef; Estrus synchronization; AI; GnRH; PGF2; Norgestomet